PANDANGAN MASYARAKAT TENTANG PANTANGAN PERNIKAHAN DI BULAN TAKEPEK (Studi Kasus Desa Kumalasa Kecamatan Sangkapura Bawean Kabupaten Gresik) - Jauharotun Nakiyah; Masrokhin Masrokhin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This thesis aims to find out and explain how the people of Kumalasa Village, Sangkapura District, Bawean Island, Gresik Regency view marriage taboos in the Takepek Month which have been believed by the people of Kumalasa Village as their tradition. This study uses a qualitative research type and uses the Islamic Legal Philosophy approach. The nature of this research is empirical because the object of this research is from the symptoms and phenomena that occur in society.The results of this study are: 1) The prohibition of marriage in the month of Dzulqa'dah or commonly called the Takepek Month in Kumalasa Village, Sangkapura District, Bawean Island, Gresik Regency is obeyed and believed by the community because of several factors. Among them are following the customs passed down from previous elders and assuming that if a marriage is held in the Takepek Month, it will bring disaster or bad luck to the family, and this belief is continuously adhered to by the community. 2) The prohibition of marriage in the Takepek Month meets the requirements for the acceptance of urf as a source of law. So it can be said that the custom of prohibiting marriage in the Takepek Month is included in the authentic urf, namely this custom does not violate sharia law, does not permit the forbidden and does not cancel the obligatory. It can be concluded that this prohibition does not conflict with the category of urf, so it can be done in everyday life and does not violate religious rules about believing in the prohibition of marriage in the Takepek Month.